Aprendizagem significativa na educação matemática: uma proposta para a aprendizagem de geometria básica - Soares, Luís Havelange (2009)
This research is to examine the potential for a learning object developed with computational resources and with the purpose of assisting in the teaching of basic geometry. We used as the theme for Basic Geometry by we know the problems in their education today We work with the hypothesis that the use of learning object the lessons of geometry can foster meaningful learning in students. The research had as its main source the meaningful learning theory of Ausubel, but also looking at media studies entered in the field of mathematics education, especially those geared to the use of technology in teaching of science, and literature about the teaching of geometry in Brazil. The study was implemented in two distinct classes of administrative spheres (public and private) of high school, both being located in the city of Campina Grande - PB. As a methodology, we use a pre-and post-test, with questions classified according to the modified taxonomy of Bloom, according to the dimensions of cognitive knowledge. We applied the first test before presenting the learning object for students and the second after the study undertaken by students and teachers. The results showed us that the learning object had a great contribution to the learning of students. In both classes there was quite a considerable growth of the medium, even among students who had low notes in both tests. The analysis in terms of cognitive dimensions also showed that even in the tests that were classified in more complex dimensions, there was a substantial increase in performance of students.